PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM (Studi Empiris pada Perusahaan Sub Sektor Pertambangan Batu Bara yang Terdaftar pada BEI) - Zaenal .; Juggi Markus (Universitas Pamulang, 2014)
Effect of Current Ratio and Debt to Equity Ratio Share Price (Empirical Study on the Company Sub Sector Coal Mine Listed on the Stock Exchange). The purpose of this study was to determine the effect the Current Ratio and Debt to Equity Ratio of the stock price either partially or simltan. This research was conducted at several companies included in the sub-sector coal. The method used in this research is quantitative descriptive. To test the hypothesis, the method used is multiple linear regression analysis using the program Statistical Package for the Social Science (SPSS). The technique used in this study using purposive sampling technique. The results showed that the data has met the classical assumptions such as normal distribution of data, there is no heteroscedasticity, multicollinearity does not occur and no autocorrelation. From the results of linear regression analysis can be partially known and simultaneous variables and Current Ratio Debt to Equity Ratio has no effect on stock prices. The coefficient of determination indicates that the price of shares in coal mining sub-sector is explained by - 0.1%, which means that the Current Ratio and Debt to Equity Ratio has no effect on stock prices. Keywords: Current Ratio, Debt to Equity Ratio and stock price.